POLA LINGKUNGAN KELUARGA PADA KEPUTUSAN MAHASISWA DALAM MEMULAI USAHA - Nabilah, Fityah (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to examine and analyze the effect of family environment patterns on student entrepreneurial decision making. The cultivation of entrepreneurial interest cannot be done immediately without education and family support that can drive a person's entrepreneurial spirit.  The family environment plays an important role in shaping students' thoughts and attitudes towards entrepreneurship. Family support, attitudes, and experiences can influence a student's interest and courage in entering the business world. This literature review is based on national and international journals with ISSN or eISSN and indexed by SINTA which are searched using Publish or Perish. The results showed that families who have an entrepreneurial background and provide positive encouragement and support significantly affect the entrepreneurial decision of a student. This study concludes that the pattern of the family environment is an important factor that encourages students' interest in entrepreneurship. Keywords: family environment, student decisions, starting a business, entrepreneurship